A vision for Social Emotional Learning and arts education policy. Issue 3 (3rd July 2021) - Edgar, Scott N.; Morrison, Bob
Abstract: This issue represents one of the first objective, collaborative pieces addressing Social Emotional Learning (SEL) across all arts content areas in diverse areas of policy. The results justify further investigation into the congruence of the arts and SEL, exploring examples of SEL instruction in the arts, and the development of consistent messages for arts education utilizing SEL. The role of SEL in arts education is still being discovered; however, the support of how the arts are a proper environment for SEL is only growing. This conclusion provides an overview of the varied levels of policy related to SEL and arts education, provides one example of artistic SEL integration (New Jersey Arts Education and SEL Learning Framework), expands on policy implications and opportunities, and concludes with strategies to utilize SEL as an advocacy tool for arts education.